Thyroid abnormalities among Down syndrome children from Kerala, India - Viswambharan, Vijitha; Vasu, Mahesh M.; Thanseem, Ismail; Poovathinal, Suresh A.; Anitha, Ayyappan (International Journal of Contemporary Pediatrics, 2019)
Down syndrome (DS), caused by trisomy of human chromosome 21, is one of the most common chromosomal abnormalities in live born infants with a prevalence rate of 1 in 700 live births. Individuals with DS usually have comorbid conditions such as thyroid dysfunction, growth retardation, diabetes mellitus and obesity. The most frequent among these are the thyroid abnormalities which range from subclinical to overt hypothyroidism, and rarely hyperthyroidism.1-3 Individuals with DS are more susceptible to thyroid disorders compared to the general population. Primary hypothyroidism, referred to as elevated TSH, is the most common thyroid abnormality in DS; secondary hypothyroidism indicated by normal/reduced TSH is extremely rare. The prevalence of hypothyroidism varies between 3-54% in adults with DS.4 The aim of this study was to examine the incidence of thyroid abnormalities among children with DS registered in a tertiary referral center for neurodevelopmental disorders and non-communicable neurological disorders in Kerala, a south Indian state. 100 children with DS in the age range of 4 months-15 years, registered at Institute for Communicative and Cognitive Neurosciences (ICCONS), Shoranur, Kerala during the period of 2012-2016, were recruited for the study. The mean age of the participants (57 males, 43 females) was 5.4±3.8 years. The diagnosis of DS was confirmed by karyotyping. All the participants were drug-naive at the time of blood collection. 500 µl of serum samples was used for thyroid function test (TFT) which measured the levels of TSH, triiodothyronine (T3) and thyroxine (T4) by chemiluminescence immunoassay (CLIA). The reference range for TSH, T3 and T4 were as follows, TSH: 0.4-4mIU/ml, T3: 70-170ng/dl, T4: 4.5-12.5mg/dl.